D-Homothetic Deformation of Normal Almost Contact Metric Manifolds - De, U.C.; Ghosh, S. (Український математичний журнал, 2012)
The object of the present paper is to study a transformation called the D-homothetic deformation of normal almost contact metric manifolds. In particular, it is shown that, in a (2n+1)-dimensional normal almost contact metric manifold, the Ricci operator Q commutes with the structure tensor ϕ under certain conditions, and the operator Qϕ – ϕQ is invariant under a D-homothetic deformation. We also discuss the invariance of η-Einstein manifolds, ϕ-sectional curvature, and the local ϕ-Ricci symmetry under the D-homothetic deformation. Finally, we prove the existence of these manifolds by a concrete example. Метою цiєї статтi є вивчення перетворення, що називається D-гомотетичною деформацiєю нормальних майже контактних многовидiв. Зокрема, показано, що у (2n+1)-вимiрному нормальному майже контактному многовидi оператор Рiччi Q комутує за певних умов iз структурним тензором ϕ, а оператор Qϕ−ϕQ є iнварiантним щодо D-гомотетичної деформацiї. Також розглянуто питання про iнварiантнiсть η-ейнштейнiвських многовидiв, ϕ-секцiйну кривину та локальну ϕ-симетрiю Рiччi при D-гомотетичнiй деформацiї. Iснування таких многовидiв доведено на конкретному прикладi.